Improving First Year Integrated Science Students’ Biological Drawing at Mfantsipim School - Dr. John Ekow Mbir Amoah; Prof. John K. Eminah; Dr Ernest I. D. Ngman-Wara; Dr James A. Azure, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
This study was action research, descriptive in nature and designed to improve first year Science students’ biological drawing skills at Mfantsipim School. The study was descriptive in nature. The main instruments used to collect data were observation schedules, interviews and a set of questionnaires. A sample of 74 students and 7 teachers were involved in the study. During the pre-intervention stages an exercise was used to assess the magnitude of students’ problems. After which, intervention activities were designed and implemented to help students improve their performance in their Biology and Integrated Science drawings to be specific. The outcome of the study revealed that students’ drawing skills had improved in Biology and Integrated Science respectively. Based on the findings, it was recommended that all stakeholders in Education should review the biology syllabus, equip teachers with the basic skills of biological drawing and organize frequent In-service Training for teachers, as this will enhance the performance of students in biological drawings in Biology and Integrated Science subjects respectively.